A method for recycling all components of waste lithium batteries

Through fine disassembly and electrochemical depowdering technology, waste lithium batteries are efficiently separated and recycled, solving the problems of low separation efficiency and high pollution in the existing technology, and achieving high recovery rate and high quality component recycling.

CN119253113BActive Publication Date: 2025-02-18XIANGTAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411765375.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing waste lithium battery recycling methods have problems such as low separation efficiency, incomplete separation, low recovery rate, and high pollution, making it difficult to achieve high efficiency and high quality recycling of each component.

Method used

Using fine disassembly and electrochemical depowder technology, the waste lithium battery is flexible and finely disassembled, and the positive and negative pulse power supply electrochemical depowder is carried out respectively. The positive and negative pulse power supply is strengthened and dissociated with free radical accelerator to achieve each group Complete separation and recycling of parts.

Benefits of technology

It realizes high efficiency and high quality recycling of various components of waste lithium batteries, with high recovery rate, high quality separation products, and no waste gas generation, reducing environmental pollution and resource waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253113B_ABST
    Figure CN119253113B_ABST
Patent Text Reader

Abstract

The invention discloses a method for recycling all components of waste lithium batteries. First, the waste lithium battery is finely disassembled to obtain a positive electrode sheet, a negative electrode sheet, a shell and a diaphragm; then, the positive and negative electrode sheets are electrochemically de-powdered by pulse current, and aluminum foil, positive electrode powder and electrolytic mother solution I are obtained after the positive electrode sheet is de-powdered, and copper foil, negative electrode powder and electrolytic mother solution II are obtained after the negative electrode sheet is de-powdered; then, the lower inorganic components of electrolytic mother solution I and electrolytic mother solution II are returned to the electrochemical de-powdering of the positive electrode sheet and the negative electrode sheet respectively as electrolytes, and the upper organic components can be used as organic fluorine raw materials; the positive electrode powder is preferentially extracted to obtain lithium salt, and then nickel salt, cobalt salt and manganese salt are extracted by nickel, cobalt and manganese; the negative electrode powder is purified and repaired to obtain lithium salt and graphite carbon powder. The present invention can realize efficient and fine separation and recovery of various components of waste lithium batteries, and the recovery rate and purity of positive electrode powder, negative electrode powder, copper foil and aluminum foil are relatively high, and the diaphragm and fluorine resources can be fully recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of waste lithium battery recycling, and in particular to a method for recycling all components of waste lithium batteries. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high voltage, good cycle performance, long life, low self-discharge, and environmental friendliness. They are widely used in electric vehicles, electronic information, energy storage and other fields. With my country's vigorous advocacy and development of new energy vehicles, the production and sales of lithium-ion batteries are increasing day by day. With the extensive use of lithium-ion batteries, a large number of waste lithium batteries are bound to be generated. Waste lithium batteries contain many valuable resources, such as nickel, cobalt, lithium, aluminum, copper, manganese and other metals, which are a very important urban mineral resource. And waste lithium batteries contain a large number of toxic and harmful substances, such as heavy metals, organic matter (methyl carbonate, ethyl carbonate), lithium hexafluorophosphate, etc. If they are directly landfilled without treatment, it will not only pose a huge threat to the natural environment and human health, but also cause a waste of important metal resources such as lithium, cobalt, and nickel. At present, waste batteries are mainly pre-processed by general crushing. The mixed materials after crushing are complex, and it is difficult to achieve complete separation of the components. The components obtained by sorting will inevitably be mixed with each other, resulting in a low grade of the separated products, and the subsequent quality recovery is more difficult; the electrode powder is generally removed by high-temperature decomposition of the binder, and there are some problems in its equipment and temperature control, and the powder removal efficiency is low, the energy consumption is high, and there are complex waste gases that are difficult to treat (containing fluorine, phosphorus, nitrogen oxides, ammonia, VOC); fluorine resources are almost not recycled. Therefore, the development of an economical and efficient waste lithium battery full component recovery process is of great significance to the resource circulation and environmental protection of waste lithium batteries. Summary of the invention

[0003] In view of the technical problems of existing waste lithium battery recycling methods such as low separation efficiency, incomplete separation, low recovery rate, and large pollution, the present invention provides a method for recycling all components of waste lithium batteries, thereby achieving high-efficiency and high-quality recycling of all components of waste lithium batteries.

[0004] The technical solution of the present invention is:

[0005] A method for recycling all components of waste lithium batteries comprises the following steps:

[0006] S1. Disassemble the waste lithium battery to obtain the positive electrode sheet, negative electrode sheet, shell and diaphragm;

[0007] S2. Electrochemically de-powder the positive electrode sheet obtained in S1 using a positive and negative pulse power supply, and add a free radical accelerator to enhance the dissociation and de-powdering, and after de-powdering the positive electrode sheet, aluminum foil, positive electrode powder and electrolytic mother solution I are obtained;

[0008] S3. The positive electrode powder obtained in S2 is subjected to lithium extraction to obtain lithium salt and nickel-cobalt-manganese slag, and the nickel-cobalt-manganese slag is then extracted by nickel-cobalt-manganese to obtain nickel salt, cobalt salt and manganese salt;

[0009] S4. Electrochemically de-powder the negative electrode sheet obtained in S1 using a single pulse power supply, and after de-powdering the negative electrode sheet, copper foil, negative electrode powder and electrolytic mother solution II are obtained;

[0010] S5. Purify and repair the negative electrode powder obtained in S4 to obtain lithium salt and graphite carbon powder;

[0011] S6. Return the lower layer of inorganic electrolyte of electrolytic mother liquor I to S2, and collect the upper layer of organic electrolyte of electrolytic mother liquor I as organic fluorine raw material; return the lower layer of inorganic electrolyte of electrolytic mother liquor II to S4, and collect the upper layer of organic electrolyte of electrolytic mother liquor II as organic fluorine raw material.

[0012] Furthermore, in step S1, the fine disassembly is to first remove the battery casing, and then separate the positive electrode sheet, the negative electrode sheet and the separator at the same time by sucking with a suction cup or pulling with a clamp.

[0013] Further, in step S2, the electrochemical de-powdering of the positive electrode sheet is performed with the positive electrode sheet as the anode, graphite as the cathode, the cell voltage is 0.5-1.5V (preferably 0.6-1.0V), and the current density is 100-200A / m 2 (Preferably 120-150A / m 2 ), the forward time is 5-15s (preferably 9-12s), the reverse time is 5-15s (preferably 6-9s), the duty cycle is 0.1-0.3 (preferably 0.20-0.25), and the total electrolysis reaction time is 1-10min (preferably 4-8min). Under the action of positive and negative pulse power supply, the current direction changes regularly, causing the aluminum foil to be oxidized and the pole powder to be reduced alternately.

[0014] Furthermore, in step S2, the electrochemical de-powdering of the positive electrode sheet uses a sulfuric acid solution containing sodium sulfate and / or potassium sulfate as the electrolyte, the concentration of sodium sulfate and / or potassium sulfate is 5-20 g / L (preferably 10-15 g / L), when sodium sulfate and potassium sulfate are present at the same time, the molar ratio of sodium sulfate to potassium sulfate is 1-2:1-1.5, and the sulfuric acid concentration is 1-10 g / L (preferably 2-5 g / L).

[0015] Furthermore, in step S2, the free radical accelerator is hydrogen peroxide, and the concentration of hydrogen peroxide is 0.1-5.0 g / L. During the electrolysis process, hydrogen peroxide can promote the system to produce more hydroxyl radicals, which produce oxidation effects on the PVDF glue and the aluminum foil surface, thereby weakening the bonding force between the pole powder and the aluminum foil.

[0016] Further, in step S4, the electrochemical de-powdering of the negative electrode sheet is performed with the negative electrode sheet as the anode and graphite as the cathode, the cell voltage is 0.5-1.5V (preferably 0.6-1.0V), and the current density is 0.1-100A / m 2 (Preferably 20-50A / m 2 ), the total electrolysis reaction time is 1-5min (preferably 3-5min).

[0017] Furthermore, in step S4, the electrochemical de-powdering of the negative electrode sheet uses a sulfuric acid solution containing sodium sulfate and / or potassium sulfate as the electrolyte, the concentration of sodium sulfate and / or potassium sulfate is 1-10 g / L (preferably 2-5 g / L), when sodium sulfate and potassium sulfate are present at the same time, the molar ratio of sodium sulfate to potassium sulfate is 1-1.5:1-2, and the sulfuric acid concentration is 0.1-1 g / L (preferably 0.2-0.5 g / L).

[0018] Furthermore, in step S5, the purification and repair is performed by graphitization at a temperature of 2000-3000°C.

[0019] The beneficial effects of the present invention are:

[0020] (1) The present invention adopts flexible fine separation to achieve complete separation and recovery of waste lithium battery separators, positive plates and negative plates, with a high recovery rate, solving the problems of positive and negative electrode powders being mixed together and copper foil and aluminum foil being incompletely separated.

[0021] (2) The present invention further improves the separation efficiency of the electrode powder and the electrode sheets by electrochemical de-powdering and adopts different pulse power supplies for the positive and negative electrode sheets, thereby improving the recovery rate and quality of the electrode powder and generating no waste gas.

[0022] (3) The present invention enables the diaphragm and electrolyte to be effectively recovered.

[0023] In short, the present invention can achieve complete separation and recovery of various components of waste lithium batteries, with high processing efficiency, low cost, and high product quality, which helps to promote the green development of the waste lithium battery resource recycling industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0026] The following examples are implemented for NCM523 type waste ternary lithium batteries. Example 1

[0027] First, the battery casing is removed and then finely separated using a suction cup to obtain the positive electrode, negative electrode, casing and separator. The recovery rates of the four are 99.27%, 98.92%, 99.35% and 99.72% respectively, and the purities are 99.63%, 99.58%, 99.41% and 99.04% respectively.

[0028] The positive electrode sheet was electrochemically de-powdered using a positive and negative pulse power supply. The positive electrode sheet was used as the anode and graphite was used as the cathode. The concentration of potassium sulfate in the electrolyte was 10 g / L, the concentration of sulfuric acid was 5 g / L, the concentration of hydrogen peroxide was 1.0 g / L, the cell voltage was 1.0 V, and the current density was 150 A / m 2 , the forward time is 10s, the reverse time is 6s, the duty cycle is 0.2, and the total electrolytic reaction time is 5min. After the positive electrode sheet is de-powdered, aluminum foil and positive electrode powder are obtained, and the separation rate is 99.16%. At the same time, electrolytic mother solution I is obtained. The upper organic electrolyte of the electrolytic mother solution I is separated and collected, and the lower inorganic electrolyte is returned to the positive electrode sheet de-powdering process. After the positive electrode powder is subjected to carbon reduction-water leaching method to extract lithium, lithium salt and nickel-cobalt-manganese slag are obtained. The nickel-cobalt-manganese slag is then extracted with nickel, cobalt and manganese by acid leaching-extraction method to obtain nickel salt, cobalt salt and manganese salt.

[0029] The negative electrode sheet was subjected to ordinary constant voltage electrochemical de-powdering, with the negative electrode sheet as the anode and graphite as the cathode. The potassium sulfate concentration in the electrolyte was 2g / L, the sulfuric acid concentration was 0.2g / L, the cell voltage was 0.6V, and the current density was 20A / m 2 The total electrolysis reaction time is 5 minutes. After the negative electrode sheet is de-powdered, copper foil and negative electrode powder are obtained, with a separation rate of 99.45%. Electrolytic mother solution II is obtained at the same time. The upper organic electrolyte of the electrolytic mother solution II is separated and collected, and the lower inorganic electrolyte is returned to the negative electrode sheet de-powdering process. The negative electrode powder is graphitized, purified and repaired, and the graphitization temperature is 2800℃ to obtain lithium salt and graphite carbon powder. Example 2

[0030] First, the battery casing is removed and then finely separated using a suction cup to obtain the positive electrode, negative electrode, casing and separator. The recovery rates of the four are 99.32%, 99.21%, 99.34% and 99.68% respectively, and the purities are 99.64%, 99.51%, 99.44% and 99.12% respectively.

[0031] The positive electrode sheet was electrochemically de-powdered using a positive and negative pulse power supply. The positive electrode sheet was used as the anode and graphite was used as the cathode. The concentration of sodium sulfate in the electrolyte was 12 g / L, the concentration of sulfuric acid was 2 g / L, the concentration of hydrogen peroxide was 0.5 g / L, the cell voltage was 1.0 V, and the current density was 120 A / m 2, the forward time is 8s, the reverse time is 5s, the duty cycle is 0.23, and the total electrolysis reaction time is 5min. After the positive electrode sheet is de-powdered, aluminum foil and positive electrode powder are obtained, and the separation rate is 99.33%. At the same time, electrolytic mother solution I is obtained. The upper organic electrolyte of the electrolytic mother solution I is separated and collected, and the lower inorganic electrolyte is returned to the positive electrode sheet de-powdering process. After the positive electrode powder is subjected to carbon reduction-water leaching method to extract lithium, lithium salt and nickel-cobalt-manganese slag are obtained. The nickel-cobalt-manganese slag is then extracted with nickel, cobalt and manganese by acid leaching-extraction method to obtain nickel salt, cobalt salt and manganese salt.

[0032] The negative electrode sheet was subjected to ordinary constant voltage electrochemical de-powdering, with the negative electrode sheet as the anode and graphite as the cathode. The sodium sulfate concentration in the electrolyte was 2g / L, the sulfuric acid concentration was 0.3g / L, the cell voltage was 0.6V, and the current density was 30A / m 2 The total electrolysis reaction time is 4 minutes. After the negative electrode sheet is de-powdered, copper foil and negative electrode powder are obtained, with a separation rate of 99.40%. Electrolytic mother solution II is obtained at the same time. The upper organic electrolyte of the electrolytic mother solution II is separated and collected, and the lower inorganic electrolyte is returned to the negative electrode sheet de-powdering process. The negative electrode powder is graphitized, purified and repaired, and the graphitization temperature is 2800℃ to obtain lithium salt and graphite carbon powder. Example 3

[0033] First, the battery casing is removed and then finely separated using a suction cup to obtain the positive electrode, negative electrode, casing and separator. The recovery rates of the four are 99.23%, 99.25%, 99.37% and 99.64% respectively, and the purities are 99.52%, 99.49%, 99.18% and 99.27% ​​respectively.

[0034] The positive electrode sheet was electrochemically de-powdered using a positive and negative pulse power supply. The positive electrode sheet was used as the anode and graphite was used as the cathode. The total concentration of sodium sulfate and potassium sulfate in the electrolyte was 15 g / L (the molar ratio of sodium sulfate and potassium sulfate was 1:1.5), the concentration of sulfuric acid was 4 g / L, the concentration of hydrogen peroxide was 1.5 g / L, the cell voltage was 1.0 V, and the current density was 120 A / m 2 , the forward time is 12s, the reverse time is 9s, the duty cycle is 0.25, and the total electrolysis reaction time is 4min. After the positive electrode sheet is de-powdered, aluminum foil and positive electrode powder are obtained, and the separation rate is 99.21%. At the same time, electrolytic mother solution I is obtained, and the upper organic electrolyte of the electrolytic mother solution I is separated and collected, and the lower inorganic electrolyte is returned to the positive electrode sheet de-powdering process. After the positive electrode powder is subjected to carbon reduction-water leaching method to extract lithium, lithium salt and nickel-cobalt-manganese slag are obtained. The nickel-cobalt-manganese slag is then extracted with nickel, cobalt and manganese by acid leaching-extraction method to obtain nickel salt, cobalt salt and manganese salt.

[0035] The negative electrode sheet was subjected to ordinary constant voltage electrochemical de-powdering, with the negative electrode sheet as the anode and graphite as the cathode. The sodium sulfate concentration in the electrolyte was 3g / L, the sulfuric acid concentration was 0.3g / L, the cell voltage was 1.0V, and the current density was 40A / m 2The total electrolysis reaction time is 4 minutes. After the negative electrode sheet is de-powdered, copper foil and negative electrode powder are obtained, with a separation rate of 99.31%. Electrolytic mother solution II is obtained at the same time. The upper organic electrolyte of the electrolytic mother solution II is separated and collected, and the lower inorganic electrolyte is returned to the negative electrode sheet de-powdering process. The negative electrode powder is graphitized, purified and repaired, and the graphitization temperature is 2800℃ to obtain lithium salt and graphite carbon powder.

[0036] Comparative Example 1

[0037] First, the battery casing is removed and then finely separated using a suction cup to obtain the positive electrode, negative electrode, casing and separator. The recovery rates of the four are 99.33%, 99.26%, 99.34% and 99.53% respectively, and the purities are 99.50%, 99.37%, 99.24% and 99.29% respectively.

[0038] The positive electrode sheet was subjected to ordinary constant voltage electrochemical de-powdering, with the positive electrode sheet as the anode and graphite as the cathode. The sodium sulfate concentration in the electrolyte was 15g / L, the sulfuric acid concentration was 4g / L, the hydrogen peroxide concentration was 1.2g / L, the cell voltage was 1.0V, and the current density was 120A / m 2 , the electrolysis reaction time is 5min. After the positive electrode sheet is de-powdered, aluminum foil and positive electrode powder are obtained, and the separation rate is 82.56%. At the same time, electrolytic mother solution I is obtained. The upper organic electrolyte of the electrolytic mother solution I is separated and collected, and the lower inorganic electrolyte is returned to the positive electrode sheet de-powdering process. After the positive electrode powder is subjected to carbon reduction-water leaching method to extract lithium, lithium salt and nickel-cobalt-manganese slag are obtained. The nickel-cobalt-manganese slag is then extracted with nickel, cobalt and manganese by acid leaching-extraction method to obtain nickel salt, cobalt salt and manganese salt.

[0039] The negative electrode sheet was de-powdered by water immersion, with a liquid-solid mass ratio of 20:1 and a water immersion time of 5 minutes. After de-powdering of the negative electrode sheet, copper foil and negative electrode powder were obtained, with a separation rate of 78.64%. Electrolytic mother liquor II was obtained at the same time, and the upper organic electrolyte of the electrolytic mother liquor II was separated and collected, and the lower inorganic electrolyte was returned to the de-powdering process of the negative electrode sheet. The negative electrode powder was graphitized, purified and repaired, and the graphitization temperature was 2800℃ to obtain lithium salt and graphite carbon powder.

[0040] Comparative Example 2

[0041] First, the battery casing is removed and then finely separated using a suction cup to obtain the positive electrode, negative electrode, casing and separator. The recovery rates of the four are 99.27%, 99.36%, 99.41% and 99.48% respectively, and the purities are 99.44%, 99.31%, 99.43% and 99.51% respectively.

[0042] The positive electrode sheet was subjected to single pulse electrochemical de-powdering, with the positive electrode sheet as the anode and graphite as the cathode. The sodium sulfate concentration in the electrolyte was 15 g / L, the sulfuric acid concentration was 4 g / L, the hydrogen peroxide concentration was 1.2 g / L, the cell voltage was 1.0 V, and the current density was 120 A / m 2 , the electrolysis reaction time is 5min. After the positive electrode sheet is de-powdered, aluminum foil and positive electrode powder are obtained, with a separation rate of 84.72%. At the same time, electrolytic mother solution I is obtained. The upper organic electrolyte of the electrolytic mother solution I is separated and collected, and the lower inorganic electrolyte is returned to the negative electrode sheet de-powdering process. After the positive electrode powder is subjected to carbon reduction-water leaching method to extract lithium, lithium salt and nickel-cobalt-manganese slag are obtained. The nickel-cobalt-manganese slag is then extracted with nickel, cobalt and manganese by acid leaching-extraction method to obtain nickel salt, cobalt salt and manganese salt.

[0043] The negative electrode sheet was de-powdered by water immersion, with a liquid-solid mass ratio of 20:1 and a water immersion time of 5 minutes. After de-powdering of the negative electrode sheet, copper foil and negative electrode powder were obtained, with a separation rate of 79.08%. Electrolytic mother liquor II was obtained at the same time, and the upper organic electrolyte of the electrolytic mother liquor II was separated and collected, and the lower inorganic electrolyte was returned to the negative electrode sheet de-powdering process. The negative electrode powder was graphitized, purified and repaired, and the graphitization temperature was 2800℃ to obtain lithium salt and graphite carbon powder.

[0044] By comparing the experimental data of the above embodiments and comparative examples, it can be seen that the process of the present invention can achieve complete separation and recovery of waste lithium battery separators, positive electrodes and negative electrodes, and the separation rate is as high as over 99%. In particular, the present invention performs specific electrochemical treatment on the positive and negative electrodes respectively, which significantly improves the separation effect.

Claims

1. A method for recycling all components of waste lithium batteries, characterized in that: The following steps are involved: S1. Disassemble the waste lithium battery to obtain the positive electrode sheet, negative electrode sheet, shell and diaphragm; S2. Electrochemically dissociate and de-powder the positive electrode sheet obtained in S1 by using positive and negative pulse power supply, and add free radical accelerator hydrogen peroxide to strengthen the dissociation and de-powdering. After the positive electrode sheet is de-powdered, aluminum foil, positive electrode powder and electrolytic mother solution I are obtained. The electrochemical de-powdering of the positive electrode sheet uses the positive electrode sheet as the anode, graphite as the cathode, and a sulfuric acid solution containing sodium sulfate and / or potassium sulfate as the electrolyte. The cell voltage is 0.5-1.5V, and the current density is 100-200A / m 2 , the forward time is 5-15s, the reverse time is 5-15s, the duty cycle is 0.1-0.3, and the total electrolysis reaction time is 1-10min; S3. The positive electrode powder obtained in S2 is subjected to lithium extraction to obtain lithium salt and nickel-cobalt-manganese slag, and the nickel-cobalt-manganese slag is then extracted by nickel-cobalt-manganese to obtain nickel salt, cobalt salt and manganese salt; S4. Electrochemically de-powder the negative electrode sheet obtained in S1 using a single pulse power supply. The electrochemical de-powdering of the negative electrode sheet uses the negative electrode sheet as an anode, graphite as a cathode, and a sulfuric acid solution containing sodium sulfate and / or potassium sulfate as an electrolyte. After de-powdering the negative electrode sheet, copper foil, negative electrode powder and electrolytic mother solution II are obtained; S5. The negative electrode powder obtained in S4 is purified and repaired by graphitization, and the graphitization temperature is 2000-3000°C to obtain lithium salt and graphite carbon powder; S6. The lower inorganic electrolyte of the electrolytic mother solution I is returned to S2, and the upper organic electrolyte of the electrolytic mother solution I is collected as an organic fluorine raw material; The inorganic electrolyte at the lower layer of the electrolytic mother solution II is returned to S4, and the organic electrolyte at the upper layer of the electrolytic mother solution II is collected as an organic fluorine raw material.

2. The method for recycling all components of waste lithium batteries according to claim 1, characterized in that: In S1, the fine disassembly is to first remove the battery casing, and then separate the positive electrode sheet, the negative electrode sheet and the separator at the same time by sucking with a suction cup or pulling with a clamp.

3. The method for recycling all components of waste lithium batteries according to claim 1, characterized in that: In S2, the cell voltage is 0.6-1.0V and the current density is 120-150A / m 2 , the forward time is 9-12s, the reverse time is 6-9s, the duty cycle is 0.20-0.25, and the total electrolysis reaction time is 4-8min.

4. The method for recycling all components of waste lithium batteries according to claim 1, characterized in that: In S2, the concentration of sulfuric acid is 1-10 g / L. When sodium sulfate and potassium sulfate do not exist at the same time, the concentration of sodium sulfate or potassium sulfate is 5-20 g / L. When sodium sulfate and potassium sulfate exist at the same time, the total concentration of sodium sulfate and potassium sulfate is 5-20 g / L, and the molar ratio of sodium sulfate to potassium sulfate is 1~2:1~1.

5.

5. The method for recycling all components of waste lithium batteries according to claim 1, characterized in that: In S2, the concentration of hydrogen peroxide is 0.1-5.0 g / L.

6. The method for recycling all components of waste lithium batteries according to claim 1, characterized in that: In S4, the cell voltage is 0.5-1.5V, and the current density is 0-100A / m 2 The total duration of the electrolysis reaction is 1-5 minutes.

7. The method for recycling all components of waste lithium batteries according to claim 1, characterized in that: In S4, the cell voltage is 0.6-1.0V and the current density is 20-50A / m 2 The total electrolysis reaction time is 3-5 minutes.

8. The method for recycling all components of waste lithium batteries according to claim 1, characterized in that: In S4, the concentration of sulfuric acid is 1-10 g / L. When sodium sulfate and potassium sulfate are not present at the same time, the concentration of sodium sulfate or potassium sulfate is 1-10 g / L. When sodium sulfate and potassium sulfate are present at the same time, the total concentration of sodium sulfate and potassium sulfate is 1-10 g / L, and the molar ratio of sodium sulfate to potassium sulfate is 1~1.5:1~2.

Citation Information

Patent Citations

  • Method for electrolytically recycling negative electrode material and copper foil of waste lithium ion battery

    CN106207301A

  • Method for leaching and recovering metal from lithium ion battery anode wastes based on electrochemical method

    CN106785174A